The European Digital Information Landscape: How Can LIBER Contribute? - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
This paper looks at a snapshot of the current state of digitisation in the information landscape. It then looks at what LIBER can contribute to that landscape through portal development, funding, identifying and documenting best practice, lobbying at a European level, and managing the transition from paper to digital delivery, including the issue of digital preservation. The paper ends by trying to identify how the user will use the digitised resources which are increasingly being made available by libraries.